Effect of soaking and misting on respiration rate, body surface temperature, and body temperature of heat stressed dairy cattle - Harner, Joseph P.; Smith, John F., 1962-; Hammond, A.K.; Miller, W.F.; Park, A.F.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Reducing heat stress is a key issue for dairy producers. Use of feedline soaking and supplemental airflow effectively reduces heat stress and increases milk production and profitability. High-pressure misting allows water to evaporate in the air, reduces air temperature, and increases relative humidity. Misting also soaks the skin of cattle, resulting in additional cooling as water evaporates from skin surfaces, similar to the cooling effect of feedline soaking. Impact of soaking frequency (5-, 10-, or 15-minute intervals) was compared to continuous high-pressure misting. Cows cooled with either system had lower respiration rates, body surface temperatures, and internal body temperatures than controls. Soaking cattle every 5 minutes or 5-minute soaking plus high-pressure misting produced similar body temperatures, but lower (P<0.01) than those when soaking occurred every 10 or 15 minutes. Skin surface temperatures from the thurl, shoulder, and rear udder were less when cattle were cooled with high-pressure misting. Cattle cooled with high-pressure misting became soaked, thus the cooling effect is the combination of cooler air and water evaporation from the skin. These results indicate that either frequent soaking (every 5 minutes) or continuous high-pressure misting that soaks the skin could be equally effective in reducing heat stress in dairy cattle.
Keywords: Dairy; Cow comfort; Cow cooling; Environment